People’s Power Policy in Legal Construction in Treason Criminal Law as Indonesian Penal Code Reform - Nur Aripkah; Eko Soponyono; Aistha Wisnu Putra (Unram Law Review, 2020)
Last year, People’s power was sounded during the presidential election period. It is still reaped the pros and cons in various circles, some called it as part of the treason, and some categorized it as a form of freedom of expression. The purpose of this article to see if the legal construction of treason criminal law is regulated under the current Penal Code, people’s power can be categorized as treason and how people’s power policies should be in the future under the legal construction of treason under criminal law. the normative point of view with the statutory approach, conceptual approach, and case approach, analyzing the concept of people’s power is not appropriate to calls as a criminal act of treason because it does not meet the juridical construction of treason under the Article 104, Article 106, and 107 of the penal code(KUHP). Likewise, in Article 191 Indonesian Penal Code Bill (RKUHP), Article 192, Article 193, and 194 RKUHP. People’s power policy in the legal construction of treason criminal law as an effort to reform the Penal Code needs to be reformulated in particular articles, later in Article 194 ofthe penal code(KUHP). The legal construction of treason criminal law then emphasized in words against the government without using the weapons.